2007
DOI: 10.1103/physrevlett.98.063201
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Temperature Dependence of the Casimir-Polder Force

Abstract: We report on the first measurement of a temperature dependence of the Casimir-Polder force. This measurement was obtained by positioning a nearly pure 87 Rb Bose-Einstein condensate a few microns from a dielectric substrate and exciting its dipole oscillation. Changes in the collective oscillation frequency of the magnetically trapped atoms result from spatial variations in the surfaceatom force. In our experiment, the dielectric substrate is heated up to 605 K, while the surrounding environment is kept near r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

48
553
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(602 citation statements)
references
References 27 publications
48
553
0
1
Order By: Relevance
“…[45][46][47][48]52 It was claimed that anomalous dependences of the residual potential difference and separation on contact on the separation distance observed in several experiments cast doubts on the measurements of the Casimir force performed to date. It was also suggested that inasmuch electrostatic calibrations are based on a fitting procedure there is no principal difference detween independent measurements of the Casimir force [20][21][22][23][24][25][26][27][28][29][30][35][36][37][39][40][41][42][43][44]71 and deriving the Casimir force by means of a fit from some much larger measured force of hypothetical origin. 31 In this respect we would like to note that the calibration consists in determination of the parameters of a setup using well established physical laws (in our case of electrostatics) and involves only well understood and precisely measured forces.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…[45][46][47][48]52 It was claimed that anomalous dependences of the residual potential difference and separation on contact on the separation distance observed in several experiments cast doubts on the measurements of the Casimir force performed to date. It was also suggested that inasmuch electrostatic calibrations are based on a fitting procedure there is no principal difference detween independent measurements of the Casimir force [20][21][22][23][24][25][26][27][28][29][30][35][36][37][39][40][41][42][43][44]71 and deriving the Casimir force by means of a fit from some much larger measured force of hypothetical origin. 31 In this respect we would like to note that the calibration consists in determination of the parameters of a setup using well established physical laws (in our case of electrostatics) and involves only well understood and precisely measured forces.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The cold molecule and the room-temperature surface are thus strongly out of equilibrium with respect to each other, so a study of the CP interaction necessitates that account be taken of the full non-equilibrium dynamics of the rotational and vibrational degrees of freedom of the cold molecule coupled to its thermal envi-ronment. In contrast, in the context of non-equilibrium forces on thermalised atoms in an environment of nonuniform temperature, as recently proposed [16] and measured [17], a study of the full internal atomic dynamics was not necessary.…”
Section: Introductionmentioning
confidence: 99%
“…For dielectric test bodies the theoretical predictions were found in agreement with the data only if the contribution of free charge carriers is omitted [33][34][35][36][37][38]. Keeping in mind that many of the experiments mentioned above were used, first, to make a selection between different theoretical approaches and, second, to constrain corrections to Newtonian gravity from the measure of agreement between the data and the predictions following from a selected approach, the constraints obtained were sometimes claimed to be of dubious merit [39].…”
mentioning
confidence: 99%
“…2 we again plot line 2 representing the constraints on the Yukawa interaction obtained from the experiment using a magnetic plate [41] independently of any selection between the different theoretical approaches to the Casimir force. In the same figure, the constraints following from the dynamic determination of the Casimir pressure by means of a micromachined oscillator [19,20] are shown by line 3, from the Casimir-less experiment [49], where the Casimir force was compensated, are shown by line 4, from measurement of the Casimir-Polder force between rubidium atoms belonging to the Bose-Einstein condensate and SiO 2 plate [35] are shown by line 5 [21], and from measurement of the Casimir force between smooth Au-coated sphere and Si plate covered with nanoscale trapezoidal corrugations [50] are shown by line 6 [51]. The constraints of Ref.…”
mentioning
confidence: 99%